Rotating cylindrical filters used in perfusion cultures: CFD simulations and experiments. (25th July 2014) - Figueredo‐Cardero, Alvio; Martínez, Edel; Chico, Ernesto; Castilho, Leda R.; Medronho, Ricardo A.
<x xml:space="preserve">Abstract</x> The particle and fluid dynamics in a rotating cylindrical filtration (RCF) system used for animal cell retention in perfusion processes was studied. A validated CFD model was used and the results gave numerical evidence of phenomena that had been earlier claimed, but not proven for this kind of application under turbulent and high mesh permeability conditions, such as bidirectional radial exchange flow (EF) through the filter mesh and particle (cells) lateral migration. Taylor vortices were shown to cause EF 10‐100 times higher than perfusion flow, indicating that EF is the main drag source, at least in early stages of RCF operation. Particle lateral migration caused a cell concentration reduction (CCR) near the filter surface of approximately 10%, contributing significantly to cell separation in RCF systems and giving evidence that the mesh sieving effect is not the sole phenomenon underlying cell retention in RCF systems. Filter rotation rate was shown to significantly affect both EF and CCR. A higher separation efficiency (measured experimentally at 2, 000‐L bioreactor scale) and an enhanced CCR (predicted by the numerical simulations) were found for the same rotation rate range, indicating that there is an optimal operational space with practical consequences on RCF performance. Experimental data of a large‐scale perfusion run employing the simulated RCF showed high cell viabilities for over 100 days, which is probably related to the fact that the computed shear stress level in the system was shown to be relatively low (below 20 Pa under all tested conditions). © 2014 American Institute of Chemical Engineers Biotechnol. Prog., 30:1093–1102, 2014